Optimization of the Samapta Patrol Unit Polres Jepara to Prevent the Crime of Motor Vehicle Theft - Ardinal, Kevin Ardiansyah (Advances in Police Science Research Journal, 2024)
This research contains about the optimization of the patrol of the Samapta Unit of the Jepara Police Resort to prevent crime of motor vehilce theft. This research is motivated by the high number of motor vehicle theft cases in the last few years, between 2018 to 2022, in the jurisdiction of the Jepara Police where routine patrols have been carried out by the Samapta Unit Jepara Police. The purpose of this research is to describe the problem of condition of organizational resources to support the Samapta unit Jepara police patrols and problem of the implementation of these patrols for the prevention of motor vehicle theft cases, so that after understanding both of these aspects, deficiencies in the Samapta Unit Jepara Police can be identified and solved with structured problem-solving step. In analyzing the research problems, it used optimization concepts, crime prevention, POAC and 6M management theory, and SWOT theory are used to analyze influencing factors. This research used a qualitative approach, as well as field research data collection through interviews, observation, and document study. The result of the research is the implementation of patrol by Samapta Unit Jepara Police for the prevention of motor vehicle theft is rated not optimal as it’s not reached the ideal conditions as stipulated by the regulations. This includes the condition of organizational resources, where personnel quality and quantity are still less than ideal, the fuel budget is insufficient to meet patrol needs, methods that are not varied, and several patrol tools that are in poor condition. In the implementation of patrols, planning is still not specific to the highest crime rate which one is theft by weighting, leadership lack direction, patrol routes are not varied enough, the use of patrol vehicles is not evenly distributed, and people who are less aware of the safety of their environment. The recommends for the Jepara resort Police leaders in the future are provide training or certification to patrol members regarding their functions, add personnel for task distribution, and increase the fuel budget to expand the patrol area and execution, with the hope of achieving more optimal results.